2018
DOI: 10.1021/acs.energyfuels.8b01348
|View full text |Cite
|
Sign up to set email alerts
|

IL-DMEE Nonwater System for CO2 Capture: Absorption Performance and Mechanism Investigations

Abstract: Dual amino functionalized ionic liquid tetramethylammonium lysinate ([N1111]­[Lys]) was synthesized and mixed with 2-[2-(dimethylamino)­ethoxy]­ethanol (DMEE) to obtain a series of nonwater absorbents for CO2 capture. The density and viscosity of the IL hybrids were measured. Using dual-vessel absorption system, CO2 absorption capacity and rate were investigated over a wide range of IL mass fractions (5–100%) to evaluate the influence of DMEE content, and 20% was chosen for further studies including influences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…As a proton acceptor, DMEE can further intensify the chemical reaction and increase the utilization of amines. 36 Interestingly, a trend is found that a larger value of k 2 is obtained in absorbents without amino load. With the increase of amine loading content, the values of k 2 for DETA-HSNs/DMEE and DETA-PSNs/DMEE display a noticeable reduction.…”
Section: Absorption Kinetic Modelsmentioning
confidence: 94%
“…As a proton acceptor, DMEE can further intensify the chemical reaction and increase the utilization of amines. 36 Interestingly, a trend is found that a larger value of k 2 is obtained in absorbents without amino load. With the increase of amine loading content, the values of k 2 for DETA-HSNs/DMEE and DETA-PSNs/DMEE display a noticeable reduction.…”
Section: Absorption Kinetic Modelsmentioning
confidence: 94%
“…Since the limit capacity of CO2 in [apbim][BF4] is only 0.5 mol per mol IL, much attention is paid on increasing the molar absorption capacity of CO2 in amino-functionalized ILs towards equivalent molar ratio or beyond. [15][16][17][18][19][20][21][22][23][24][25][26] One popular approach is to tether the amino group to the anion of IL such as trihexyl(tetradecyl)phosphonium methioninate ([P66614][Met]) and trihexyl(tetradecyl)phosphonium prolinate ([P66614][Pro]), and make the anion charge centre and amino group in close proximity (Scheme 2). [15,16] As a result, a 1 : 1 stoichiometry of CO2 uptake was obtained through formation of relatively stable carbamic acid.…”
Section: High Capacity Of Comentioning
confidence: 99%
“…The naturally-occuring amino-acid anions containing an additional amine group (e.g., lysinate, asparaginate, glutaminate) and trihexyl(tetradecyl)phoshonium cation ([P66614]) were used for the fabrication of functionalized ILs for beyond one molar absorption of CO2. [17][18][19] The cation effect was also studied by replacement of [P66614] with trihexyl(tetradecyl)ammonium [N66614] when the anion was fixed as lysinate ([Lys]) anion. [20] [16] Protic ILs, formed through proton transfer from a Brønsted acid to a Brønsted base, are able to be designed as flexible molecules with small molar mass and show potential on high utake of CO2.…”
Section: High Capacity Of Comentioning
confidence: 99%
“…DMAEE has similar properties to MDEA, but it has a lower viscosity than MDEA. Meng et al suggested that DMAEE was a good substitute for MDEA [5]. Du et al screened 36 kinds of novel reagents and found that DMAEE and DGA aqueous solution had the best resistance to high temperature oxidation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Absorption capacity data were obtained once per second in each absorption experiments. Nonlinear fitting was performed by using equation (5) through orthogonal distance regression. The model parameters qe and k1 can be obtained by fitting to the experiment.…”
mentioning
confidence: 99%